SYNTHESIS OF MFI ZEOLITE NANOSHEET USING NOVEL BIFUNCTIONAL ORGANIC COMPOUND AS STRUCTURE- AND CRYSTAL- DIRECTING AGENT - Nindita Sahdarani, Dyah
MFI zeolite is a microporous crystalline aluminosilicate material that is widely used as shape-selective catalyst. As a catalyst, in fact MFI zeolite has low efficiency due to the thick prismatic hexagonal-crystal type with size over 3000 nm leading to the phenomenon of diffusion limitation. In order to solve this proble, we have designed the bifunctional organic compoung that has the ability to direct the MFI zeolite structure and crystal shape towards nanoscare (< 100 nm). The diquaternary ammonium ion, (C3H7N+(CH2)5N+(C3H7)3), hereby term later as diquat-C5, was employed as structure- and crystal-directing agent. The synthesis of MFI zeolite with nanosheet crystal morphology was completed using hydrothermal treatment after mixing the precursors such us tetraethyl orthosilicate (TEOS), aluminium hydroxide (Al(OH)3), sodium hydroxide (NaOH), water and diquat-C5. X-ray diffraction (XRD), physisorption, scanning electron microscope (SEM), and solid state Nuclear Magnetic Resonance (NMR) were employed to confirm the finished prodct. Result showed that MFI zeolite with nanosheet crystal morphology was successfully synthesized at 150°C for 5 days. A conventional MFI zeolite with prismatic hexagonal morphology was also synthesized for comparison.